A failed tentative to design a super carbonic anhydrase having the biochemical properties of the most thermostable CA (SspCA) and the fastest (SazCA) enzymes. (2nd November 2015) - De Luca, Viviana; Del Prete, Sonia; Carginale, Vincenzo; Vullo, Daniela; Supuran, Claudiu T.; Capasso, Clemente
Abstract: Carbonic anhydrases (CAs, EC 4.2.1.1) catalyze a simple reaction in all life domains: the carbon dioxide hydration to bicarbonate and protons: CO2  + H2 O →   + H + . Six different, genetically distinct CA families are known to date, the α-, β-, γ-, δ-, ζ- and η-CAs. Bacteria encode for CAs belong to the α-, β- and γ-classes. Recently, our groups investigated the presence of CAs in two bacteria belonging to the genus Sulfurihydrogenibium living in hot springs all over the world, at temperatures of up to 110  °C. The α-CAs from Sulfurihydrogenibium yellowstonense and Sulfurihydrogenibium azorense, denominated SspCA and SazCA, respectively, are highly thermostable, maintaining a good catalytic activity even after being heated for a prolonged period. Moreover, SazCA was to be the fastest CA known to date with a k cat value of 4.40  ×  10 6 s −1 and a k cat / K M value of 3.5  ×  10 8 M −1 s −1 . SspCA also showed a good catalytic activity for the same reaction, with a k cat value of 9.35  ×  10 5 s −1 and a k cat / K M value of 1.1  ×  10 8 M −1 s −1, proving that the "extremo-α-CAs" are between the most effective CAs known to date. Here, we describe a failed tentative to obtain a super-CA, SupCA, by combining the amino acid sequence of SazCA and SspCA. To achieve this goal we introduced six His residues in N -terminal sequence of SspCA. However the obtained SupCA showed lower catalytic activity and thermostability compared to both extremophilic enzymes from which it has been designed. We rationalized the biochemical reasons of this failure, which may be useful to design enzymes with a better catalytic activity.